Utilização de amido reticulado como matriz para imobilização do fármaco diclofenaco de sódio - Iurckevicz, Genice (2014)
In this study, the cassava starch was crosslinked with sodium trimetaphosphate (TMFS). In this matrix was incorporated the sodium diclofenac drug, where it was evaluated its release kinetics, with the objective of verifying the possibility of employing the cassava starch microparticules crosslinked with TMFS in controlled release of drugs. It was used an experimental design which tested two concentrations of starch (-1 = 5%; 1 = 10%), two concentrations of crosslinkers (-1 = 15%; 1 = 30%) and two periods of time (-1= 2; 1 = 8 hours) besides, four repetitions for the main point which corresponds to concentration of starch 7,5%, crosslinkers 22,5% and time of 5 hours, a total of twelve experiments. It was found that the only factor that significantly influenced in a confidence level of 90% in incorporation of sodium diclofenac was the concentration of starch, the incorporation is greater when the starch concentration approaches 10%. It was selected the sample which incorporated the greatest amount of sodium diclofenac in each group with a different concentration of starch (A5R15t2; A10R30t2 and A7,5R22,5t5 4) for characterization by infrared spectroscopy, thermal analysis, cross-linking density, scanning electronic microscopy and also for the kinetic study of the release. It was verified that the sample with the highest crosslinking (A5R15t2) also incorporated more sodium diclofenac, the A7,5R22,5t5 sample showed the highest amount of phosphate groups not linked (no effective crosslinking) and had the lowest amount of sodium diclofenac incorporated. The crosslinked samples presented a higher thermal resistance compared to pure starch, crosslinked samples with the sodium diclofenac had higher thermal stability than pure starch, but lower than the samples crosslinked starch. The kinetic models that best represented the release of the drug were: first-order, Peppas and Higuchi, for Peppas model it was calculated the diffusion coefficient (n) of the system, obtaining values of 0,14; 0,26 and 0,12 for samples A5R15t2DS; A7,5R22,5t5DS and A10R30t2DS respectively, these values are different from those reported in the literature, the variation is attributed to the different particle sizes obtained and difficult solubility of sodium diclofenac, aspects confirmed by scanning electronic microscopy.